The psychopedagogical aspect of catechesis - Ghiuță, Ștefan-Adrian (Technium Social Sciences Journal, 2022)
Catechesis, the most important tool for knowing God, is the act that involves man from the age of awareness until the last moment before meeting God. Catechesis, as an apostolic work, as a mission work, requires knowledge in the field, faith and a pure heart, but also a method of sharing the teaching of the Christian faith, that is, a set of rules to be able to make it as well understood as possible.